Waqf dan Ibtidā’ dalam Mushaf Al-Qur’an - Istiqomah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
This paper discusses the differences in waqf and ibtidā 'between the Indonesian Standard Manuscripts, Bombay Manuscripts, Holy Manuscripts and Medina Manuscripts based on the waqf signs used in each Mushaf, and their effect on meaning. This research uses a descriptive method. The results of this study conclude that the difference between waqf and ibtidā 'between Indonesian standard manuscripts, Bombay manuscripts, Holy manuscripts and Medina manuscripts lies in the signs used, also in the way they are placed. From these differences give birth to an understanding that may be different from the understanding that arises from waqf and ibtidā 'in other lafazh in the same verse. It's just that the difference in meaning that is born from the difference between the waqf and ibtidā 'signs is not contradictory